Low-emission hydrogen: global value chain opportunities for latecomers and industrial policy challenges - Tilman Altenburg; Rita Strohmaier (Journal of International Business Policy, 2025)
To meet decarbonization targets, demand for low-emission hydrogen is increasing. A considerable share of supply will come from latecomer countries. We study how latecomer countries and firms participate in the emerging global low-emission hydrogen economy and how industrial policies can help maximize societal benefits. This requires a specific conceptualization of industrial policy: First, the latecomer condition calls for specific policy mixes, as latecomers typically cannot build on established innovation systems and network externalities, and rather need to combine FDI attraction with measures strengthening absorptive capacity and ensuring knowledge transfer from FDI to domestic firms; second, low-emission hydrogen is a policy-induced alternative that requires creating entirely new firm ecosystems while competing with lower-cost emission-intensive incumbent technologies. Hence, industrial policies need to account for enhanced coordination failure and internalization of environmental costs. We analyze the published national hydrogen strategies of 20 latecomer economies and derive a novel typology differentiating four hydrogen-specific industrial development pathways. For each pathway, we assess entry barriers and risks, identify the policies suggested in the country strategies, and discuss how likely those are to be successful. The novel pathway typology and comparison of associated policy mixes may help policymakers maximize the gains of hydrogen investments.
Keywords: 650; Low-emission hydrogen; Industrial policy; Latecomer economy; National hydrogen strategies; Industrial upgrading